The anguish of snails: Native American folklore in the West - Toelken, Barre, author; Utah State University Press, publisher (Colorado State University. Libraries, 2003)
Within a framework of performance theory, cultural worldview, and collaborative research, Toelken examines Native American visual arts, dance, oral tradition (story and song), humor, and patterns of thinking and discovery to demonstrate what can be gleaned from Indian traditions by Natives and non-Natives alike. Winner of the Chicago Folklore Prize.
Prologue: the snail's clues -- Cultural patterns in Native American folklore: an introduction -- Visual patterns of performance: arts -- Kinetic patterns of performance: dance -- Oral patterns of performance: story and song -- Patterns and themes in Native humor -- Cultural patterns of discovery -- Epilogue: "gleaning" and the active audience.
Keywords: Indians of North America -- West (U.S.) -- Folklore; Folklore -- Performance -- West (U.S.); Folklore -- West (U.S.) -- Classification; Oral tradition -- West (U.S.)